Diseño e implementación de procedimientos técnicos para 6 ensayos relacionados con materiales cerámicos como parte del SGC del LabCIVCO según la norma INRTE-ISO/IEC 17025:2005 - Zeledón-Vargas, Daniela (Instituto Tecnológico de Costa Rica, 2010)
This graduation project is aimed on technical and logistical implementation methodologies for the accreditation of six test LabCIVCO, which are part of the Quality Management System, based on compliance with the regulations of the Costa Rican Accreditation Entity (ECA) and INTE standard: ISO / IEC 17025:2005, which seeks to standardize the procedures involved in each test. An important part of this project was the development of instructional based on ASTM and ANSI standards, and conducting training for all test and performance tests for three of them. This with the objective of evaluating the procedures established in each instruction to be executed correctly. Was performed an analysis of the results of tests and concluded that technicians are familiar with testing methodologies but there is lack of interest from them and why mistakes are made that alter the results, also recommended buy of air conditioning to maintain controlled environmental conditions when performing the tests and help improve the quality of the laboratory and to promote technical competence.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2010.
Keywords: Legislación; Estándares; Ingeniería en Construcción; Aseguramiento de la Calidad; Normas ASNSI; Normas ASTM